RESISTENSI DAN PENERIMAAN GURU TERHADAP KURIKULUM 2013 DI KOTA PAREPARE - Rustan Efendy (IAIN PAREPARE, 2015)
This study discusses the relationship between competence and teacher responses to the implementation of Curriculum 2013 in the Elementary School in Parepare. This type of research is descriptive qualitative data collection methods such as structured interviews, questionnaires, and documentation study. Once the data is collected, verified and tested its validity. The results showed that elementary school teachers in Parepare have proven competent at teaching certificate, however the degree of their competen faced with technical problems in the implementation phase as access to information. They responded positively to the implementation of Curriculum 2013, with the record prior to the enforcement of government must be prepared for all possibilities including the setting up of facilities and pre-supporting means.